Role of Information and Communications Technology in Improving Equity and Quality of Education in India - Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
Education is a fundamental right and is indispensable for the achievement of sustainable development. The role of ICT has enhanced and supplemented classroom learning and is an important tool to provide quality education for all. A good-quality education throughout the lifecycle, from early childhood through adulthood, can be a liberating process for individuals and it can act as a leveler and equalizer within the society. India has also made noteworthy progress towards the goal of Education for All' in the past years. Starting from Sarva Shiksha Abhiyan to the Right to Education Bill, the focus has been to ensure equal access to quality education for the children. ICT has been a significant enabler in enabling this movement. The New Education Policy 2020 (NEP), recognizes the importance of technology in aiding teachers, bridging the language barrier between teachers and students, creating digital libraries, popularizing language learning as well as ensuring greater access to education. Technology has made the learning space expand beyond the traditional classrooms. This has helped individuals to avail opportunities to continue learning throughout their lifetime. With the help of affordable smartphones, digital platforms, the geographical and economical barriers have been reduced to some extent. Advancements like QR embedded textbooks have made it possible to access high-quality educational content for the learners and teachers. ICT has the potential to alleviate or remove some of the barriers or constraints that prevent women and girls from accessing educational opportunities, such as illiteracy, poverty, time scarcity, sociocultural factors, mobility, and relevancy, leading to women empowerment and gender equality. It has brought education into homes and non-traditional learning spaces, where it can be accessed by girls and women. The digital tools and platforms have made education more inclusive as well, where children with special needs can study in a normal classroom environment. The country has acknowledged that EdTech isn't just about digitizing the content, but rather about providing unlimited access to learning which can be personalized and customized. This paper focuses on how technology has played a crucial role in bringing education to all and in improving equity and gender equality in India.
Keywords: 330